Constructing research questions doing interesting research - Alvesson, Mats; Sandberg, Jorgen (Los Angeles Sage, 2013)
"All researchers want to produce interesting and influential theories. A key step in all theory development is formulating innovative research questions that will result in interesting and significant research. Traditional textbooks on research methods tend to ignore, or gloss over, actual ways of constructing research questions. In this text, Alvesson and Sandberg develop a problematization methodology for identifying and challenging the assumptions underlying existing theories and for generating research questions that can lead to more interesting and influential theories, using examples from across the social sciences. Established methods of generating research questions in the social sciences tend to focus on 'gap-spotting', which means that existing literature remains largely unchallenged. The authors show the dangers of conventional approaches, providing detailed ideas for how one can work through such problems and formulate novel research questions that challenge existing theories and produce more imaginative empirical studies. Constructing Research Questions is essential reading for any researcher looking to formulate research questions that are interesting and novel."--Publisher's website.
1. Research questions: a core ingredient in developing interesting theories -- 2. The context of constructing and formulating research questions -- 3. Gap-spotting: the prevalent way of constructing research questions in social science -- 4. A critical evaluation of gap-spotting research: does it lead to interesting theories? -- 5. Problematization as a methodology for generating research questions -- 6. Applying the problematization methodology in practice -- 7. Why does gap-spotting dominate when it reduces the chance to create interesting theories? -- 8. Constructing interesting research questions: problematization and beyond.
Includes bibliographical references (pages [129]-138) and index.
Keywords: Social sciences -- Research -- Design; Questionnaires -- Design